THE IMPACT OF THE UNSTABLE ECONOMIC ENVIRONMENT ON THE FINANCIAL STABILITY OF ENTERPRISES: ANALYSIS AND CHALLENGES - BORETSKA, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The modern world is characterized by constant changes and instability of the economic environment, which poses new and complex challenges to enterprises. The instability of the economy affects various aspects of the activities of enterprises, but it has a particularly significant effect on their financial stability.Financial stability is one of the main prerequisites for the successful and stable operation of the enterprise in any conditions. The need to ensure financial stability is due to the growing risks and threats that accompany the instability of the economy. Changes in macroeconomic indicators, exchange rate fluctuations, unfavorable legislative decisions and other economic factors can significantly affect the financial condition of the enterprise.The article examines the factors of instability of the economic environment, such as inflation, changes in currency rates, the risk of political instability, and others, and their impact on the financial stability of enterprises. An analysis of the risks and challenges faced by enterprises in an unstable economic environment was made. An analysis of the impact of an unstable economic environment on the financial stability of enterprises was carried out. Within the framework of this study, the factors of instability of the economic environment were analyzed, their possible consequences for the financial condition of enterprises, as well as recommendations were provided regarding strategies for managing financial stability in the conditions of an unstable economic environment. Research is aimed at helping enterprises to respond more effectively to changes and ensure the stability of their financial position.
Keywords: financial stability; enterprises; analysis; challenges; legislation; macroeconomic factors; political risks; export; economic security